B2B online platforms development for formation of an effective business environment - I. A. Puzanova; P. A. Averyanova (E-Management, 2022)
Today, more than ever, there is a need for comprehensive support for intercompany electronic B2B trade, as an effective business environment for the functioning of small and medium-sized businesses. The main objective of this study is to identify the problems hindering the development of Internet commerce in the B2B segment, and to provide recommendations for its development in Russia under the sanction’s restrictions imposed by the West. The main barriers to automation and digitalisation of sales and purchases at the intercompany level of interaction are: 1) the prevalence of a conservative idea of doing business in B2B, unwillingness to change outdated business processes; 2) the erroneous judgment that launching your own B2B online solutions is very expensive and difficult; 3) the idea that creating your own B2B portal or marketplace is advisable only for large businesses; 4) underestimation of the enormous advantages and benefits that digitalisation provides for small and medium-sized businesses. Based on the analysis of these barriers, directions for more active involvement of small and medium-sized businesses in e-commerce are formulated. Namely: 1) training of business representatives in the specifics of organizing and implementing automated procurement and sales processes; 2) the development of online platforms that bring together many sellers and suppliers of products, logistics and financial companies, since this tool does not require investments in the creation of an Internet platform and does not bear the cost of maintaining its own IT department; 3) development of comprehensive support for electronic commerce of small and medium-sized businesses, including onboarding; 4) modernization of the regulatory framework for regulating electronic commerce based on the use of information and telecommunication technologies, since electronic commerce is regulated by the Commonwealth of Independent States Model Law “On Electronic Commerce”; 5) creation of state support system for electronic commerce, as it is a driver for the development of the national economy.